Analisis Preferensi Konsumen terhadap Penggunaan Produk Skincare Korea Selatan dan Lokal - Nur Fitri Andriani; Achma Hendra Setiawan (Universitas Diponegoro, 2020)
This study discusses the effect of consumer preferences on the use of products skincare South Korean and local. The purpose of this study was to analyze the differences between consumer preference variables and product attributes skincare. In addition, it is also to analyze consumer choices between products skincare South Korean or local and respondents' considerations in choosing products skincare. This study was conducted on 100 respondents aged 15 to 54 years. The data analysis used was the Chi Square test and descriptive statistics. The results showed that 74 respondents chose products skincare local and 26 respondents usedproducts skincare South Korean. Chi Square test analysis shows that there are differences between brand attributes, benefits, packaging, price and brand ambassadors on consumer preferences, and main ingredient attributes that have no difference with consumer preferences. A total of 74 respondents chose products skincare local and 26 respondents used products skincare South Korean.